Interface characteristics of polystyrene melts in free-standing thin films and on graphite surface from molecular dynamics simulations. (5th May 2017) - Lee, Sanghun; Lyulin, Alexey V.; Frank, Curtis W.; Yoon, Do Y.
Abstract: Interface characteristics of polystyrene (PS) melts in free-standing thin films and on a graphite surface were investigated by molecular dynamics simulations employing an explicit all-atom force field. The calculated surface tension is in good agreement with experiment, which provides good support for the force field parameters employed. In the polymer/vacuum free-surface region, the density profile exhibits an enrichment of phenyl groups relative to the backbone alkyl groups at the outermost low-density free surface, but this free surface is followed by a layer of relatively depleted phenyls and enriched alkyls of ca. 7 Å thickness. In the free surface, the phenyl-ring normal vectors and backbone chain vectors are both preferentially oriented along the film surface, in agreement with available experiments. At the polymer/graphite interface, the backbone chain vectors are strongly oriented along the graphite surface whereas the orientation distribution of phenyl-ring normal vectors exhibits two maxima along the nearly parallel (20°) and the perpendicular direction to the graphite-surface normal. A densely packed structure is formed at the PS-graphite interface, which strongly decreases the segmental chain mobility, in contrast to the enhanced segmental mobility in the free-surface region. Graphical abstract: Highlights: MD simulations of polystyrene thin films yield asurface tension in good agreement with experiments. Segregation of phenyls to outermost surface with phenyl-ring planes preferentially oriented perpendicular to the surface. An interfacial layer exists adjacent to surface, with depleted phenyls and concomitantly enriched backbone alkyl groups. Two preferential orientations of phenyl-ring planes on graphite, aligned nearly parallel and perpendicular to the surface. Chain dynamics are much slower in the graphite interface, while faster in the free-surface, than in the bulk.